In situ Chemical Profiling and Imaging of Cultured and Natural Cordyceps sinensis by TOF-SIMS - Liu, Qian-Bao; Lu, Jing-Guang; Jiang, Zhi-Hong; Zhang, Wei; Li, Wen-Jia; Qian, Zheng-Ming; Bai, Li-Ping (Frontiers in Chemistry, 2022)
Based on a two-layered media embedding sample preparation, a surface-sensitive time-of-flight secondary ion mass spectrometry (TOF-SIMS) approach was developed for in situ chemical profiling and imaging of medicinal food of both natural (NCS) and cultured Cordyceps sinensis (CCS) in this research. More than 200 components were tentatively identified and imaged in NCS and CCS at the same time. Mass spectrometry imaging revealed that most components have even distributions in caterpillars of Cordyceps sinensis, while TAGs, DAGs, MAGs, and FAs only have distributions outside caterpillars' digestive chambers. This is the first time that components were in situ imaged for Cordyceps sinensis to exhibit the chemical distributions which have never been achieved by other analytical techniques so far. In addition, relative quantification of TOF-SIMS data showed that CCS has comparable proportions of amino acids, nucleosides, monosaccharides, sphingolipids, sterols and other principles to NCS except for fatty acids, glycerides and glycerophospholipids. Quantitative NMR confirmed high amounts of TAGs and DAGs in CCS, indicating reliable relative quantification of TOF-SIMS. Additionally, chemometric analysis of TOF-SIMS data exhibited high chemical similarity between CCS and NCS.